MERCAPP campesino: aplicación web para facilitar la distribución de productos por parte de agricultores y la reducción de intermediarios - Acuña Hernandez, Karol Giseth (Universidad Antonio Nariño, 2021)
Currently, the world is facing one of the biggest humanitarian crises with a significant impact on the global economy. Among those affected is the group of peasants who lack the means of transportation and technology to get their product from the crop to the collection centers. To support this process, it was proposed to build a web application that facilitates the purchase and sale of products between the peasantry and the final consumer, including its transportation. Technologies such as Javascript and Firebase for the backend and React.js for the frontend were used to develop the application. In addition, Scrum was used as a development methodology.